2015
DOI: 10.1002/2015jc010893
|View full text |Cite
|
Sign up to set email alerts
|

Field evidence of beach profile evolution toward equilibrium

Abstract: An equilibrium framework is used to describe the evolution of the cross‐shore profile of five beaches (medium grain size sand) in southern California. Elevations were observed quarterly on cross‐shore transects extending from the back beach to 8 m depth, for 3–10 years. Transects spaced 100 m in the alongshore direction are alongshore averaged into nineteen 700–900 m long sections. Consistent with previous observations, changes about the time average profile in many sections are captured by the first mode empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 58 publications
(119 reference statements)
0
50
1
Order By: Relevance
“…An empirical beach state model (Ludka et al, ; Yates, Guza, & O'Reilly, ; Figure d) previously calibrated at sites shown in Figure c as well as at Camp Pendleton, estimates erosion potential of the observed waves using equilibrium concepts (Wright et al, ; Wright & Short, ). Hourly waves alongshore averaged over each monitoring site in Figure c, then averaged across all sites are used as model input.…”
Section: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…An empirical beach state model (Ludka et al, ; Yates, Guza, & O'Reilly, ; Figure d) previously calibrated at sites shown in Figure c as well as at Camp Pendleton, estimates erosion potential of the observed waves using equilibrium concepts (Wright et al, ; Wright & Short, ). Hourly waves alongshore averaged over each monitoring site in Figure c, then averaged across all sites are used as model input.…”
Section: Historical Perspectivementioning
confidence: 99%
“…The equilibrium energy E eq is the wave energy that causes no profile change for a given beach state. A single set of optimized parameters for change rate coefficients C + and C − (used for beach face accretion and erosion, respectively), and equilibrium energy slope and intercept a and b , were found for times and locations not detectibly influenced by nourishment, reef, canyon, shoal, or lagoon mouth, within the intensive monitoring effort (Ludka et al, ). The model reasonably reproduced profile observations during unnourished times at all selected sites, shown to behave similarly; however, these curated sections of beach cumulatively span less than 10 km, and are all in the southernmost third of the 300‐km domain investigated in the present study.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Red indicates El Niño winters. (c) Beach state estimated using observed waves and published model coefficients [ Ludka et al , ]. The model, insensitive to initial conditions after a brief transient, is initialized with A = 0 on 1 January 2009.…”
Section: Wave Observationsmentioning
confidence: 99%
“…At MSL, Cardiff, Torrey, and Imperial are from Ludka et al []. Solana is from Group Delta Consultants [].…”
Section: Introductionmentioning
confidence: 99%
“…Yates et al, 2009) or other functions of wave energy, such as (log ( )) 2 (Banno & Kuriyama, 2014). Ludka et al (2015) found that utilising wave energy instead of various functions of H and T resulted in least normalised mean square errors in their model. In Yates et al…”
Section: Wave Energymentioning
confidence: 99%